How do you solve sqrt(2x+3)-sqrt( x+1) =1?

1 Answer
Apr 29, 2018

The two solutions are x=3 and x=-1.

Explanation:

Isolate one of the radicals, square both sides, isolate the other radical, then square both sides again:

sqrt(2x+3)-sqrt(x+1)=1

sqrt(2x+3)=1+sqrt(x+1)

(sqrt(2x+3))^2=(1+sqrt(x+1))^2

2x+3=1+2sqrt(x+1)+x+1

x+1=2sqrt(x+1)

(x+1)/2=sqrt(x+1)

(x+1)^2/2^2=(sqrt(x+1))^2

(x^2+2x+1)/4=x+1

x^2+2x+1=4x+4

x^2-2x-3=0

(x-3)(x+1)=0

x=3,-1

Those are the solutions to the problem. Hope this helped!